2019
DOI: 10.1097/inf.0000000000002240
|View full text |Cite
|
Sign up to set email alerts
|

Specimen Pooling as a Diagnostic Strategy for Microbiologic Confirmation in Children with Intrathoracic Tuberculosis

Abstract: Three-hundred four young children with suspected pulmonary tuberculosis had a gastric aspirate, induced sputum and nasopharyngeal aspirate collected on each of 2 consecutive weekdays. Specimens collected on the second day were pooled in the laboratory for each child individually. The diagnostic yield by Xpert and culture from pooled specimens was not significantly different to a single gastric aspirate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Finally, we tested each sample separately so as to investigate the yield from each sample; additional studies using a single Ultra test on combined samples are needed. However, a recent study reported that pooling specimens (IS, gastric lavage, NPA) did not result in improved diagnostic accuracy from Xpert or culture compared with a single specimen (21).…”
Section: Rifampicin Resistance and Time To Resultsmentioning
confidence: 95%
“…Finally, we tested each sample separately so as to investigate the yield from each sample; additional studies using a single Ultra test on combined samples are needed. However, a recent study reported that pooling specimens (IS, gastric lavage, NPA) did not result in improved diagnostic accuracy from Xpert or culture compared with a single specimen (21).…”
Section: Rifampicin Resistance and Time To Resultsmentioning
confidence: 95%
“…For instance, a metaanalysis by Chew and colleagues showed that the collection of a single pooled sample over 24 hours increased the diagnostic yield compared to 'spot' or early morning sputum collection (Chew et al, 2019). Alternative methods such as pooling two induced sputum specimens from the same patient (Mpagama et al, 2012) or continuous overnight collection of sputum (Murphy et al, 2017) have shown utility in increasing the diagnostic yield, although this was not demonstrated in children (Walters et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates the difficult clinical dilemma in resource-limited settings, and we would argue that access to even a single Ultra test would be a great step forward to assist clinicians in their clinical judgment and management. It also indicates the importance of identifying the method with the highest yield/cost ratio and the need to consider approaches such as pooled specimen testing that may increase the diagnostic yield from a single test or allow multiple respiratory specimens to be tested with one Ultra cartridge (5, 6).…”
mentioning
confidence: 99%
“…Various respiratory specimen types can be collected, such as gastric aspirates (GA), IS and NPAs, and each have their own advantages and disadvantages. NPA may be easier to obtain, but culture and genotypic yields are lower compared with IS or GA (3, 6). IS and GA are more invasive, but diagnostic yields are higher (3, 6), and in considering the optimal combination of specimens, clinicians need to consider cultural or other barriers to obtain specimens in addition to their combined diagnostic yield (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation